Pengaruh Jenis Pengaduk Dan Waktu Fermentasi Terhadap Fermentasi Nira Nipah Menjadi Bioetanol Menggunakan Yeast Saccharomyces Cereviceae - Nst, Khoirul Amru; S, Maria Peratenta; Chairul, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bioethanol is a chemical that is produced from plant raw materials containing starch, sugar and cellulose through a process of fermentation and distillation is an alternative fuelthat is environmentally friendly and renewable nature. One of the raw materials for bioethanol production are Nypa sap. Availability of land wide enough Nypa in Indonesia (700,000 ha) as well as a fairly high sugar content (18-19%) makes the Nypa sap is a potential to be processed into bioethanol. Flow patterns and the degree of turbulence is an important aspect that affects the quality of mixing is dependent on several factors such as the geometry of the tank, the physical properties of the fluid and the Impeller. Fermentation time very big influence on the activity of yeast because the longer the fermentation, the more the number increasingly active yeast or yeast to proliferate. The purpose of the study to convert the sugar in the Nypa sap is fermented into bioethanol and observe the effect of impeller and fermentation time on ethanol produced using Sacharomyces cereviceae. Through the process of fermentation using yeast Sacharomyces cereviceae, glucose is converted into ethanol and carbon dioxide. Preparation is done with the starter yeast inoculum Sacharomyces cereviceae at 10% so that the yeast fermentation medium is able to adapt and ready to ferment. Fermentation takes place in batches with a volume of 2 liters of fermentation medium, variations impeller Paddle, Pitched Blade Turbine, Disc Turbine and variations of fermentation time 24, 36, 48, 60 and 72 hours. Stirring speed of 150 rpm and temperature of fermentation at room temperature (25 - 300C). Ethanol concentration was analyzed by using Gas Chromatography. The optimum fermentation process is shown on the Impeller Pitched Blade Turbine fermentation time of 48 hours with yield obtained 89,86% and ethanol concentrations obtained 10.72% (v / v) or 84.60 mg / ml.Keywords: Bioethanol, Nypa Sap, Saccharomyces Cerevisiae, Impeller, Flow Pattern.